2003
DOI: 10.1177/0739986303025002002
|View full text |Cite
|
Sign up to set email alerts
|

Dual Ethnicity and Depressive Symptoms: Implications of Being Black and Latino in the United States

Abstract: This study investigated the expression of depressive symptoms in adolescents who are of Afro-Latino descent. Levels of expression of depressive symptoms were compared for four groups of adolescents in Grades 7 through 12 residing in the United States: European Americans, African Americans, Latinos, and Afro-Latinos. One hypothesis is that Afro-Latinos should exhibit higher levels of depressive symptoms than either African Americans or Latinos by virtue of being double minorities. An alternative hypothesis is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…In one of the few existing national studies of Latino youth (age 11–15), Saluja and his colleagues (2004) found that Latino youth had higher rates of depressive symptoms (22%) than white (18%), Asian American (17%), and African American (15%) youth. Other studies also consistently find higher rates of depression among Latino youth—especially Mexican American and Afro-Latinos—than among other ethnic groups (Choi et al, 2006; Mikolajczyk et al, 2007; Ramos et al, 2003). Although no national data are available on the prevalence of anxiety disorders or anxiety-related problems among Latino youth, studies also suggest that Latino youth experience significantly higher levels of anxiety than whites but not African Americans (Glover et al, 1999; Roberts et al, 2006).…”
mentioning
confidence: 85%
“…In one of the few existing national studies of Latino youth (age 11–15), Saluja and his colleagues (2004) found that Latino youth had higher rates of depressive symptoms (22%) than white (18%), Asian American (17%), and African American (15%) youth. Other studies also consistently find higher rates of depression among Latino youth—especially Mexican American and Afro-Latinos—than among other ethnic groups (Choi et al, 2006; Mikolajczyk et al, 2007; Ramos et al, 2003). Although no national data are available on the prevalence of anxiety disorders or anxiety-related problems among Latino youth, studies also suggest that Latino youth experience significantly higher levels of anxiety than whites but not African Americans (Glover et al, 1999; Roberts et al, 2006).…”
mentioning
confidence: 85%
“…In a follow-up study of the National Chicano Study, Codina and Montalvo (1994) documented a significant relationship between phenotype and depression to the extent that darker U.S.-born Chicanos had higher symptoms of depression than lighter-skinned Chicanos. Similarly, Ramos et al (2003) compared levels of depression between black Latino high school students to reports of depression among non-black Latinos, African Americans, and white students. They found higher levels of depression among black Latinos than for youth of the other racial and ethnic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, limited research exists on the effect that race and discrimination may have on the psychological well-being of Latino youth. Some researchers who have focused on the effect of race on psychological well-being have found that darker-skinned and black Latinos tend to have worse mental health than their whiter Latino peers (Borrell et al 2006; Ramos, Jaccard, and Guilamo-Ramos 2003; Szalacha et al 2003). Another line of research has examined the relationship between discrimination and the mental health of Latino youth and found that discrimination is a powerful stressor, detrimental to the psychological well-being of this population (Borrell et al 2006; Major et al 2007; Rivera 2005).…”
mentioning
confidence: 99%
“…Structural factors such as anti-immigrant policies and poverty, and the inequities and discriminatory practices that accompany these factors impact Latino mental health and well-being. For example, the Latino population has been identified as a high risk group for depression and anxiety connected to poverty, poor housing conditions, and rigid work demands (Magana & Hovey, 2003); and poor mental health related to discrimination (Araujo & Borrell, 2006; Ramos, Jaccard, & Guilamo-Ramos, 2003). …”
mentioning
confidence: 99%